2019
DOI: 10.1021/acsphotonics.9b00120
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Far- to Near-Field Channeling in Synergetic Multiscale Antennas

Abstract: Enhancing light−molecule interactions requires the efficient transfer of energy between the laboratory macroscale and the molecule nanoscale. Multiscale designs have been proposed as a means to efficiently connect these two worlds. Metallic sphere-segment void (SSV) cavities constitute plasmonic substrates in which light wavelength scale cavity-like modes and nanoscale roughness operate in conjunction as a multiscale antenna to provide larger surface-enhanced Raman scattering efficiency than the two mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this article, we report a work along with the direction of Van Duyne's strategy on borrowing SERS effect and based on the strategy of cascading optical coupling by the hierarchical structure integrating a subwavelength optical antenna and a deep-subwavelength optical antenna for high-efficiency optical coupling. [18,54,61,62] We theoretically design an ATRcascading nanostructure-enhanced Raman spectroscopy (ATRc-NERS) configuration for the much higher sensitivity. The SERS-active nanostructures such as bare Au or Ag NPs, SHINs, further focus the subwavelength light into the deep-subwavelength region, that is, the nanostructure-substrate nanogaps.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In this article, we report a work along with the direction of Van Duyne's strategy on borrowing SERS effect and based on the strategy of cascading optical coupling by the hierarchical structure integrating a subwavelength optical antenna and a deep-subwavelength optical antenna for high-efficiency optical coupling. [18,54,61,62] We theoretically design an ATRcascading nanostructure-enhanced Raman spectroscopy (ATRc-NERS) configuration for the much higher sensitivity. The SERS-active nanostructures such as bare Au or Ag NPs, SHINs, further focus the subwavelength light into the deep-subwavelength region, that is, the nanostructure-substrate nanogaps.…”
Section: Background and Motivationmentioning
confidence: 99%
“…It is reported that the electromagnetic field intensity is inversely proportional to the distance parameter, which means that the effective SERS signal is generated on the premise that the molecule is located in the confined area around the plasmonic material [10]. Various types of SERS substrate structures ranging from nanoparticle (NP) aggregates [11][12][13][14][15], multidimensional structure [16][17][18][19][20] and composite substrate [21][22][23][24][25][26][27][28][29] were prepared to explore the better enhancement factor (EF) under various conditions. Among them, the cavity system has been paid more and more attention because of its unique light trapping characteristics [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%